Financial remuneration is positively correlated with the number of clinical activities: an example from diabetes management in Alberta community pharmacies. (27th February 2017) - Bharadia, Rajan; Lorenz, Kathleen; Cor, Ken; Simpson, Scot H
Abstract: Objective: To determine whether use of a compensation plan to remunerate pharmacists for clinical pharmacy services was associated with the number of diabetes management activities provided. Methods: Alberta pharmacists were asked about compensation plan use and frequency they provide a list of 80 diabetes management activities. Key findings: A total of 168 community pharmacists responded to the survey. When compensation plan use, diabetes-specific training, practice characteristics and additional authorizations were incorporated into a factorial ANOVA, pharmacists who used the compensation plan reported a mean of 42.9 (95% CI 39.4 to 46.4) diabetes management activities, while those who did not reported a mean of 29.9 (95% CI 21.4 to 38.4) activities ( P = 0.016). Conclusions: After considering other important influencing factors, use of the compensation plan is positively correlated with the number of diabetes management activities pharmacists provided.